COVID-19 and transport. A review of factors of relevance to the design of measures and their effects worldwide - Shortall, Ruth; Mouter, Niek; Van Wee, Bert (European Journal of Transport and Infrastructure Research, 2022)
The COVID-19 pandemic has led to the introduction of transport-related policy measures worldwide. In this paper, we review the literature on factors that are important for the design of those measures, and their effects on safety, physical and mental health, economy and environment. We conclude that factors underlying the introduction of transport related measures are related to the broader discussion on COVID-19 measures (e.g. on social distancing). This makes it impossible to determine the independent influence of determinants aimed at transport on the effects (virus spread, economy, well-being). Furthermore, the effects of measures appear to differ strongly between countries. Important determinants for these effects are (1) socio-economic factors, (2) cultural factors, (3) political factors and (4) individual factors. In addition, the extent to which people can work at home appears to be very important for the introduction and effectiveness of COVID-19 measures. In the category of 'cultural factors', the degree to which people have a 'sense of civic responsibility' and trust in the government and institutions plays a major role in the compliance with advice and coercive measures. Furthermore, experiences with previous viruses appear to have made a positive contribution to COVID-19 policies that are successful at containing the virus. Finally, individual factors play a role in the compliance with COVID-19 measures. For example, a pro-social attitude is associated with better compliance. And: if people rate the effectiveness of such measures higher, they are more likely to act on them. The paper also provides recommendations for policy and further research.